Local quantification and characterisation represents a basic tool for integrated residential solid waste management (2010)
A sampling and characterization plan for residential solid waste (SW) produced in the city of Cali in Colombia was developed between January and September 2006; this required designing an undisclosed strategy in the country and the results showed the need for an adjustment to the current SW Colombian classification scheme. The available sampling frame made a two-stage sampling plan necessary, block side (BS) being the first stage and household BS the second. A 0.39 kg/(person-day) solid waste per-capita production (PCP) was found, which increased with socioeconomic status. Food waste was produced most, a large part consisting of cooked food. Waste from personal hygiene items was a third category, although this is not currently a category which is included in Colombian Technical Standard –RAS 2000. Although characterization techniques are used worldwide, the results showed the relevance of available sampling frame-based local characterization, using local data for sampling methods and associated sample size selection.